Life in the treetops : adventures of a woman in field biology - Lowman, Margaret (Yale University Press, 1999)
"In this book a pioneer canopy scientist describes the mysteries of the treetops - their inhabitants, flowers and fruits, growth and mortality, patterns of diversity, and plant and animal interactions. Margaret Lowman writes about different canopy access techniques in conjunction with the scientific hypotheses she was addressing while using each one. She also portrays the life of a field biologist from a woman's perspective: what it was like to juggle a demanding career with marriage, housewifery, motherhood, and single parenthood."--Jacket